Electronic Cigarette: Good guy or bad guy? - Lima Menezes, Iasmim (2021)
Objective: to discuss the health effects caused by the use of electronic cigarettes. Material and Methods: A search was performed in the PubMed/Medline database of complete articles published in the last 10 years. A total of 21 articles were used, according to the established inclusion criteria, with a higher prevalence of cross- sectional studies. Results: It was verified that electronic cigarettes may even help in the cessation of conventional smoking, however, their users are not exempt from suffering systemic health complications. They present toxic substances and should not be considered totally safe and harmless. Conclusions: Further studies are still needed to determine the implications of the use of this electronic device on the health of its users in the long term.